Kurikulum Merdeka: Hakikat Kurikulum dalam Pendidikan - Diah Lestari; Masduki Asbari; Eka Erma Yani (Journal of Information Systems and Management (JISMA), 2023)
Education can be divided into three main paths, namely formal, nonformal, and informal. Formal education is education at school that is obtained regularly, systematically, in stages, and by following clear requirements. The aim of this research is to find out the meaning of the curriculum not only for students but also for teachers. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narrativites from the UPI Curriculum and Education Technology Youtube channel entitled “ The Nature of curriculum in Education “. Results of this study explained that the curriculum ia a goal to achieve the competencies you want to achieve and the Curriculum ia also a tool for assessing the extent to which the effectiveness of the series of learning systems implemented by the goverment can be delivered well by teachers and can be understood by students